Tinjauan Kelengkapan Pengisian Formulir Permintaan Informasi Medis di Rumah Sakit Permata Pamulang - Ima Rusdiana; Holidah Holidah; Tasya Kamila (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
The medical information request form is the consent given by the patient or their closest family after receiving a complete explanation regarding the medical action that will be carried out on the patient. The aim of this study was to analyze the completeness of filling out medical information request forms. The method used in this research is descriptive research using a sample of 50 medical information request forms. The sampling technique used in this research was total sampling. The results of the research showed that filling in the patient's identity at Gem Pamulang Hospital was almost completely complete with a percentage of 98% and almost nothing was incomplete with a percentage of 2%, almost half of the important reports were complete with a percentage of 29.5 and more than half were incomplete with the percentage is 70.5% and the author authentication is partially complete with a percentage of 24%, and most of it is incomplete with a percentage of 76%.